Optimization Measures for Land Occupation Scale of Fully Automatic Metro Vehicle Base - WEN Pengzhe; KANG Zhe; XU Daoliang; GAO Shijie (Chengshi guidao jiaotong yanjiu)
［Objective］The application of fully automatic operation (FAO) technology has led to a further increase in metro vehicle base land scale and in newly built FAO metro lines, as well as the FAO transformation of existing ordinary lines. Therefore, it is urgent to carry out in-depth researches on measures to reduce the size of FAO vehicle bases. ［Me-thod］Starting from the planning process of conventional metro vehicle bases, and combined with the special requirements brought by FAO technology, factors affecting land occupation scale of FAO vehicle bases are summarized. Considering the development of FAO technology and vehicle maintenance modes, optimization measures to reduce land occupation scale of FAO vehicle bases are proposed. ［Result & Conclusion］There are no special design requirements for large and overhaul maintenance garage of fully automatic metro vehicles. By conducting sufficient researches on resource sharing schemes in the line network planning stage, and adopting the balanced maintenance system in the design and operation stages, the number of vehicle base maintenance position amounts can be effectively reduced ; by giving full play to technical advantages, FAO lines can effectively reduce the number of spare vehicles and carry out mainline parking design, thus reduce the number of vehicle base parking positions; the width of the uncovered parking inspection garage can be effectively reduced by dividing the parking and inspection areas in width direction, dividing the parking area into protection zones every 3 to 5 tracks, and dividing the inspection area into protection zones every 2 to 3 tracks. In special cases, the use of sliding vehicle blocks can appropriately reduce the length of parking inspection garage.